The Genus Adonis as an Important Cardiac Folk Medicine: A Review of the Ethnobotany, Phytochemistry and Pharmacology - Shang, Xiaofei; Miao, Xiaolou; Yang, Feng; Wang, Chunmei; Li, Bing; Wang, Weiwei; Pan, Hu; Guo, Xiao; Zhang, Yu; Zhang, Jiyu (Frontiers in Pharmacology, 2019)
The genus Adonis L. (Ranunculaceae), native to Europe and Asia, comprises 32 annual or perennial herbaceous species. Due to their cardiac-enhancing effects, Adonis spp. have long been used in European and Chinese folk medicine. These plants have been widely investigated since the late 19th century, when the cardiovascular activity of Adonis vernalis L. was noted in Europe. The present paper provides a review of the phytochemistry, biological activities and toxicology in order to highlight the future prospects of the genus. More than 120 chemical compounds have been isolated, with the primary components being cardiac glycosides as well as flavones, carotenoids, coumarins and other structural types. Plants of the genus, especially Adonis vernalis L. and Adonis amurensis Regel & Radde, their extracts and their active constituents possess broad pharmacological properties, including cardiovascular, antiangiogenic, antibacterial, antioxidant, anti-inflammatory and acaricidal activities, and exhibit both diuretic effects and effects on the central nervous system. However, most plants within the 32 species have not been comprehensively studied, and further clinical evaluation of their cardiovascular activity and toxicity should be conducted. Additionally, overexploitation combined with habitat destruction has resulted in the rapid decrease of the resources necessary to study these species. This review provides new insight into the genus and lays a solid foundation for further development and utilization of Adonis.